Size-controlled synthesis of anatase nanobrush structures with higher crystal density. (October 2017) - Stodolny, M.; Zagrodnik, R.; Nowaczyk, G.; Jurga, S.
Graphical abstract: Highlights: Application of AAO as template for TiO2 nanowires synthesis. Non-hydrolytic sol-gel method as an implementation of TiO2 into AAO template. Vertical anchorage of TiO2 nanowires to the polymer support. Photocatalytic oxidation of methyl orange correlate with geometric surface area of TiO2 . Abstract: Titanium dioxide was synthesized in multistep process applying of AAO (Anode Aluminum Oxide) as a template. The TiO2 nanowires were obtained by deposition of titanium precursors inside the pores of AAO membranes (non-hydrolytic sol-gel technique), calcined at 875 K with subsequent removal of alumina matrix by leaching it with phosphoric acid. During the AAO synthesis, it was proved that the electrical work can serve as the unified factor influencing the amount of formed AAO. The diameters of obtained titania nanowires were consequence of used AAO membranes. The higher density of titania elementary cell was observed for all synthesized nanostructures. It was confirmed by XRD and SAED measurements. The TiO2 nanowires attached vertically to polymer disc (50 mm diameter) were used in photocatalytic decomposition of methyl orange. All nanomaterials showed ten times higher photocatalytic activity than P-25. High photoactivity of obtained material is related to external area of vertically aligned titania nanowires.